An international perspective of out-of-hospital cardiac arrest and cardiopulmonary resuscitation during the COVID-19 pandemic - Ong, Justin (Am J Emerg Med, 2021)
BACKGROUND: Out-of-hospital cardiac arrest (OHCA) accounts for a substantial proportion of sudden cardiac events globally, with hundreds of thousands of cases reported annually in the United States. The mortality rate of patients who suffer OHCA remains high despite extensive utilization of resources. OBJECTIVES: We aim to describe the current landscape of OHCA during the COVID-19 pandemic and provide an overview of the logistical challenges and resuscitation protocols amongst emergency medical service (EMS) personnel. DISCUSSION: Recent studies in Italy, New York City, and France characterized a significant increase in OHCA incidence in conjunction with the arrival of the 2019 coronavirus disease (COVID-19) pandemic. The presence of the pandemic challenged existing protocols for field resuscitation of cardiac arrest patients as the pandemic necessitated prioritization of EMS personnel and other healthcare providers' safety through stringent personal protective equipment (PPE) requirements. Studies also characterized difficulties encountered by the first responder system during COVID-19, such as dispatcher overload, increased response times, and adherence to PPE requirements, superimposed on PPE shortages. The lack of guidance by governmental agencies and specialty organizations to provide unified safety protocols for resuscitation led to the development of different resuscitative protocols globally. CONCLUSIONS: The ongoing COVID-19 pandemic modified the approach of first responders to OHCA. With the rise in OCHA during the pandemic in several geographic regions and the risks of disease transmission with superimposed equipment shortages, novel noninvasive, adjunct tools, such as point of care ultrasound, warrant consideration. Further prehospital studies should be considered to optimize OHCA and resource management while minimizing risk to personnel.